Pengaruh Pendapatan, Religiuisitas, Pelayanan, dan Pemasaran Terhadap Profitabilitas Bank Syariah dengan Keputusan Nasabah Melakukan Pembiayaan Pemilikan Rumah Syariah Sebagai Variabel Intervening - Riska Inggit Avianti (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of income level, religiosity, service, and marketing on the profitability of Islamic banks with the customer's decision to finance Islamic home ownership (PPRS) as an intervention variable. The population in this study are Islamic bank customers in the city of Bandung who carry out Islamic home ownership financing. The sample in this study was 100 respondents. The research method used is quantitative research methods. This study uses primary data and secondary data obtained from the results of questionnaires and financial statements of each Islamic bank in Bandung. Data analysis in this study used the PLS method and the Sobel test using the SmartPLS 3.0 program